Crime and planning: building socially sustainable communities - Paulsen, Derek J. (CRC Press, 2013)
"Introduction Few in the fields of urban planning or urban design would argue with the fact that crime is a serious and important community issue. In addition, few would dispute that the form and layout of the built environment has a large and significant influence on crime by creating opportunities for it and, by extension, shaping community crime patterns. However, when asked if they consider crime when making planning and design decisions, few planners or designers would answer in the affirmative. The potential implications of ignoring crime in the decision-making process are profound. In 2008 alone more than 11 million crimes were reported in the United States, resulting in direct financial losses of between $17 and $26 billion, in addition to incalculable personal loss.1 Crime has also been shown to be associated with decreased housing values, reduced rent prices, residential instability, home owners' decisions to move, and general neighborhood decline.2 As a result, the public consistently views crime as one of the top public issues facing the country. Since 1997 crime has consistently been ranked by more than 85 percent of survey respondents as either the "top issue" or "important but not the top issue," outscoring such issues as taxes on the middle class, jobs, the budget deficit, and global trade issues.3 Whether considered an economic or a social issue, crime is an important issue for communities, one that affects and is affected by the form, layout, and functioning of the built environment. This leads to the question: If crime is such an important community issue, why do planners and designers fail to consider it in their decision-making processes? Why a Disconnect?"--